2015
DOI: 10.1371/journal.pone.0130950
|View full text |Cite
|
Sign up to set email alerts
|

Citrus tristeza virus (CTV) Causing Proteomic and Enzymatic Changes in Sweet Orange Variety “Westin”

Abstract: Citrus Tristeza disease, caused by CTV (Citrus tristeza virus), committs citrus plantations around the world and specifically attacks phloem tissues of the plant. The virus exists as a mixture of more or less severe variants, which may or may not cause symptoms of Tristeza. The objective of this study was to analyze the changes caused by CTV in the proteome of stems of sweet orange, as well as in the activity and gene expression of antioxidant enzymes. The CTV-infected sweet orange displayed mild symptoms, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Nitrogen is a major constituent of both host cell and viral nucleic acids and proteins. Elevated viral proteins and nucleic acid content together with known CTV influence on protein profile and activity (Dória et al ., ) might lead to increased N levels in leaves, similar to the general increase of total N in virus‐infected plants reported for other host–virus combinations (Sinha & Srivastava, ). Some studies have suggested the relationship between elevated leaf N concentration and susceptibility to virus infection to be caused by the formation of virus particles, despite significant correlation between these two parameters (Iqbal et al ., ; Ashfaq et al ., ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nitrogen is a major constituent of both host cell and viral nucleic acids and proteins. Elevated viral proteins and nucleic acid content together with known CTV influence on protein profile and activity (Dória et al ., ) might lead to increased N levels in leaves, similar to the general increase of total N in virus‐infected plants reported for other host–virus combinations (Sinha & Srivastava, ). Some studies have suggested the relationship between elevated leaf N concentration and susceptibility to virus infection to be caused by the formation of virus particles, despite significant correlation between these two parameters (Iqbal et al ., ; Ashfaq et al ., ).…”
Section: Discussionsupporting
confidence: 81%
“…SODs are the most important group of metalloenzymes and are considered as the first defence against ROS. Many authors have found changes in SOD activity in different plant species and cultivars in response to virus infection (Clarke et al, 2002;Siddique et al, 2014;D oria et al, 2015). In some cases the activity rises, in others SOD activity is suppressed, but it seems that it is initially genotype-dependent and that resistant genotypes develop higher SOD activities upon the virus infection as a plant strategy to restrict virus multiplication.…”
Section: Discussionmentioning
confidence: 99%
“…Based on transcriptomic analyses, 334 genes in Mexican lime ( C. aurantifolia ) were found to respond to infection by a severe CTV isolate (T305), and 28% of these regulated genes were related to the stress and defense responses (Gandía et al ., ). A proteomic study showed that CTV infection causes changes in the protein profile/activity and gene expression of antioxidant enzymes in sweet orange ( C. sinensis ) (Dória et al ., ). Another proteomic analysis revealed that rootstock–scion crosstalk also influences citrus response to CTV.…”
Section: Introductionmentioning
confidence: 97%
“…Huanglongbing (HLB) Proteomics [142] Proteomics; nutrient analysis [143] Proteomics; enzyme activity; reverse genetic [144] Transcriptomics ( Microarray) [145] Transcriptomics (RNASeq) [137,138,146] Transcriptomics (RNASeq); proteomics; FISH [147] Transcriptomics (qPCR); physiology; hormone content [148,149] Phytophthora spp Metabolomics [150] Transcriptomics (RNASeq) [151] Xanthomonas citri Metabolomics [152] Proteomics [153,154] Proteomics; structural study; enzyme activity; reverse genetic [155] Citrus Tristeza Virus Metabolomics; physiology; hormone content [156,157] Proteomics; enzyme activity [158] Reverse genetic [159,160] Transcriptomics (qPCR) [161,162] Transcriptomics (RNASeq) [146,163] Mal secco Proteomics; metabolomics; physiology [164] Transcriptomics (SSH) [40] Unlike to other citrus diseases, such as Phytophthora spp., [137,138,142,145], sometimes together with multidisciplinary approaches [139,165,166], identifying many candidates and regulated genes. Other works are focused to identify potential genotypes tolerant to CTV by qPCR [162] or to highlight the differentially expressed transcripts (DETs) after combined infection with different virus (HLB and CTV) [146].…”
Section: Disease Molecular Approach Referencementioning
confidence: 99%